Development and placement of the food industry in Ukraine - Dzynhar, Maksym; Kovalova, Olena (My University, 2020)
The food industry is an integral part of the economics of Ukraine, which is a crucial section of the national economy. The leading role of the industry is due to the fact that it makes a decisive contribution to the creation of material and technical base of all social production, as well as most of the material values intended to meet the needs of the population. Providing the population with quality food is one of the main areas of socio-economic development of any country. Ukraine has all the objective prerequisites for creating a highly advanced food industry that is able to meet domestic food needs and generate significant foreign exchange earnings from its global market. Харчова промисловість є невід'ємною частиною економіки України, яка є важливим розділом національної економіки. Провідна роль галузі пов'язана з тим, що вона вносить вирішальний внесок у створення матеріально-технічної бази всього суспільного виробництва, а також більшості матеріальних цінностей, призначених для задоволення потреб населення. Забезпечення населення якісною їжею є одним з основних напрямків соціально-економічного розвитку будь-якої країни. В Україні є всі об'єктивні передумови для створення високорозвиненої харчової галузі, яка здатна задовольнити внутрішні потреби в продуктах харчування та генерувати значні валютні надходження на світовому ринку.
Keywords: харчова промисловість; food industry; sectors of food industry; development; factors of development; placement; кафедра ділової іноземної мови та міжнародної комунікації; галузі харчової промисловості; розвиток; фактори розвитку; розміщення